Electronically Driven Regioselective Iridium‐Catalyzed C−H Borylation of Donor‐π‐Acceptor Chromophores Containing Triarylboron Acceptors. Issue 46 (23rd July 2020) - Rauch, Florian; Krebs, Johannes; Günther, Julian; Friedrich, Alexandra; Hähnel, Martin; Krummenacher, Ivo; Braunschweig, Holger; Finze, Maik; Marder, Todd B.
Abstract: We observed a surprisingly high electronically driven regioselectivity for the iridium‐catalyzed C−H borylation of donor‐π‐acceptor (D ‐π‐A) systems with diphenylamino (1 ) or carbazolyl (2 ) moieties as the donor, bis(2, 6‐bis(trifluoromethyl)phenyl)boryl (B( F Xyl)2 ) as the acceptor, and 1, 4‐phenylene as the π‐bridge. Under our conditions, borylation was observed only at the sterically least encumbered para ‐positions of the acceptor group. As boronate esters are versatile building blocks for organic synthesis (C−C coupling, functional group transformations) the C−H borylation represents a simple potential method for post‐functionalization by which electronic or other properties of D ‐π‐A systems can be fine‐tuned for specific applications. The photophysical and electrochemical properties of the borylated (1‐(Bpin)2 ) and unborylated (1 ) diphenylamino‐substituted D ‐π‐A systems were investigated. Interestingly, the borylated derivative exhibits coordination of THF to the boronate ester moieties, influencing the photophysical properties and exemplifying the non‐innocence of boronate esters. Abstract : That's the spot ! A surprisingly high regioselectivity was observed for an iridium‐catalyzed C−H borylation of conjugated donor‐π‐acceptor systems with bis(2, 6‐bis(trifluoromethyl)phenyl)boryl (B( F Xyl)2 ) as the acceptor group. The borylated system exhibits an unexpected hypsochromic shift of the emission from toluene to THF, likely due to coordination to the boronate ester moieties (see figure).